Application of the radionuclide 210Pb in glaciology – an overview - Heinz W. Gäggeler; Leonhard Tobler; Margit Schwikowski; Theo M. Jenk (Journal of Glaciology, 2020)
210Pb is an environmental radionuclide with a half-life of 22.3 years, formed in the atmosphere via radioactive decay of radon (222Rn). 222Rn itself is a noble gas with a half-life of 3.8 days and is formed via radioactive decay of uranium (238U) contained in the Earth crust from where it constantly emanates into the atmosphere. 210Pb atoms attach to aerosol particles, which are then deposited on glaciers via scavenging with fresh snow. Due to its half-life, ice cores can be dated with this radionuclide over roughly one century, depending on the initial 210Pb activity concentration. Optimum 210Pb dating is achieved for cold glaciers with no – or little – influence by percolating meltwater. This paper presents an overview which not only includes dating of cold glaciers but also some special cases of 210Pb applications in glaciology addressing temperate glaciers, glaciers with negative mass balance, sublimation processes on glaciers in arid regions, determination of annual net snow accumulation as well as glacier flow rates.